Innovative anode catalyst designed to reduce the degradation in ozone generation via PEM water electrolysis. (December 2018) - Yu, Jyun-Wei; Jung, Guo-Bin; Chen, Chi-Wen; Yeh, Chia-Chen; Nguyen, Xuan-Vien; Ma, Chia-Ching; Hsieh, Chung-Wei; Lin, Cheng-Lung
Abstract: Membrane electrode assemblies (MEAs) using commercial PbO2 powder as the anode catalyst to generate ozone via water electrolysis were traditionally adopted. We found that commercial MEAs evinced the typical degradation phenomenon after a current interruption and restart during operation, where the performance degraded and partially recovered after the resumption of current. In this study, homemade MEAs using PbO2 powder and additives were developed, which ameliorated the degradation phenomenon. SEM and XRD analysis were used to compare the anode structure of the homemade to commercial MEAs after short–and long–term operation post–resumption of current after an interruption. Highlights: Anode with proportions of PbO2 /Nafion of 9:1 and catalyst loading of 30 mg/cm 2 was utilized with additives for ozone generation. Ratio of additives acid and PTFE 5:1 leads to highest current generation, better ability to mitigate current degradation after current interruption/restart test. Homemade MEA performed better than commercial MEA because additive-acid was escaped from the catalyst, leaving more space beneficial for the electrochemical reaction.